Legal Implications of the Sale of Inherited Land Without the Consent of All Heirs from the Perspective of Islamic Law and Positive Law - Ayu Permata Sukma; Artiyanto Artiyanto; Susi Kusmawaningsih; Dicky Andrian (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
The research examines the legal implications of the sale of inherited land conducted without the consent of all heirs, viewed from the perspectives of Islamic law and positive law in Indonesia. The issue arises from the frequent occurrence of unilateral transactions over jointly owned inheritance property, which often leads to disputes due to a lack of legal awareness and improper understanding of the status of undivided inheritance. This research is positioned as a normative-empirical legal study, aiming to analyze both legal norms and their implementation in society. The discussion is carried out through a comparative approach between Islamic law, which emphasizes principles of justice, maslahah, and mutual consent (ridha), and positive law, particularly the Civil Code and agrarian regulations, which require agreement among co-owners for valid legal transactions. The findings indicate that, under Islamic law, such transactions are considered fasid (defective) and potentially invalid due to the absence of full authority and consent, while under positive law, they may be declared null and void or voidable, and can give rise to civil liability, including compensation claims. Both legal systems fundamentally uphold the principle of joint ownership and the necessity of collective approval, thereby highlighting the importance of legal certainty and protection for all heirs. This study also underscores the need for greater legal awareness and stricter supervision in land transactions involving inherited property